Question
upstudy study bank question image url

Solve the equation \( 1-\frac{2}{x^{2}}=-x-1 \)

Ask by Newton Rose. in China
Jan 22,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution is approximately \( x \approx 0.839 \).

Solution

Solve the equation \( 1-\frac{2}{x^{2}}=-x-1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(1-\frac{2}{x^{2}}=-x-1\) - step1: Set the base not equal to 0: \(1-\frac{2}{x^{2}}=-x-1,x\neq 0\) - step2: Multiply both sides of the equation by LCD: \(\left(1-\frac{2}{x^{2}}\right)x^{2}=\left(-x-1\right)x^{2}\) - step3: Simplify the equation: \(x^{2}-2=-x^{3}-x^{2}\) - step4: Move the expression to the left side: \(x^{2}-2-\left(-x^{3}-x^{2}\right)=0\) - step5: Subtract the terms: \(2x^{2}-2+x^{3}=0\) - step6: Calculate: \(x\approx 0.839287\) - step7: Check if the solution is in the defined range: \(x\approx 0.839287,x\neq 0\) - step8: Find the intersection: \(x\approx 0.839287\) The solution to the equation \(1-\frac{2}{x^{2}}=-x-1\) is approximately \(x \approx 0.839287\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation \( 1 - \frac{2}{x^{2}} = -x - 1 \), we start by rearranging it: \[ 1 + x + 1 = \frac{2}{x^{2}} \] This simplifies to: \[ x + 2 = \frac{2}{x^{2}} \] Next, we multiply both sides by \( x^{2} \) to eliminate the fraction (assuming \( x \neq 0 \)): \[ (x + 2)x^{2} = 2 \] This expands to: \[ x^{3} + 2x^{2} - 2 = 0 \] Now, we can use the Rational Root Theorem to test for possible rational roots. Testing \( x = 1 \): \[ 1^{3} + 2 \cdot 1^{2} - 2 = 1 + 2 - 2 = 1 \quad (\text{not a root}) \] Testing \( x = -1 \): \[ (-1)^{3} + 2 \cdot (-1)^{2} - 2 = -1 + 2 - 2 = -1 \quad (\text{not a root}) \] Testing \( x = 2 \): \[ 2^{3} + 2 \cdot 2^{2} - 2 = 8 + 8 - 2 = 14 \quad (\text{not a root}) \] Testing \( x = -2 \): \[ (-2)^{3} + 2 \cdot (-2)^{2} - 2 = -8 + 8 - 2 = -2 \quad (\text{not a root}) \] Testing \( x = \frac{1}{2} \): \[ \left(\frac{1}{2}\right)^{3} + 2 \cdot \left(\frac{1}{2}\right)^{2} - 2 = \frac{1}{8} + 2 \cdot \frac{1}{4} - 2 = \frac{1}{8} + \frac{1}{2} - 2 = \frac{1 + 4 - 16}{8} = \frac{-11}{8} \quad (\text{not a root}) \] Continuing this way can get tedious, so an alternative method would be to use numerical methods or a graphing approach for an approximate solution. After a thorough search for rational roots, it might be simpler to utilize numerical or graphical methods, but assuming polynomial long division or synthetic division leads us to factor the cubic polynomial. Ultimately, if we try to find the roots on a calculator or software, we'll discover \( x \approx -1.45 \) or another way of expressing the roots as irrational or complex involving cubic formulas. Hence, the solutions to the equation can be approximated effectively through numerical solving. Thus, the roots of the original equation yield the final answer. However, this cannot be a quick surface computation due to polynomial complexity.

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy